2020
DOI: 10.3329/agric.v18i1.49465
|View full text |Cite
|
Sign up to set email alerts
|

Millet-Jute-T. Aman Cropping Pattern for Increasing System Productivity in the Active Brahmaputra-Jamuna Floodplain Chars

Abstract: Increasing system productivity in a planned way is an important base for attaining food security, where bringing marginal land like Charland under intensive crop cultivation is highly desirable. The field trial was conducted in the Charland of the Jamuna River under Saghataupazilla of Gaibandha during 2017- 18 & 2018-19 to increase the productivity and profitability through the development of three crops-based improved cropping patterns instead of the local practice (double-crop). Three crops based improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Cropping intensification from single to double increase the system REY by two to four times higher in rice-based cropping system [28][29][30], even varied 9-34% from rice-rice to rice-non rice crop based cropping systems [31] in India. Cropping system intensification from double (rice-rice or rice-wheat) to triple cropping system (Wheat-Mungbean-T. Aman) increased the system REY by 10-75% in the High Ganges River Floodplain and Madhupur tract of Bangladesh [5,32,33]; three times more in the active Brahmaputra-Jamuna Floodplain Chars of Bangladesh [34], but 42% more wheat equivalent yield (WEY) in India [35], as well 82% higher system REY when compared to double to four crop-based systems [36]. In other, reported that cropping system intensification from three to four crop-based system increased system REY by 38-44% across the different agroecological zones of Bangladesh [37][38][39], similar to our study, whereas it was lower by 26% [40] and much higher (81%) as reported by Islam et al [41] compared to our study.…”
Section: Crop and System Rice Equivalent Yieldmentioning
confidence: 99%
“…Cropping intensification from single to double increase the system REY by two to four times higher in rice-based cropping system [28][29][30], even varied 9-34% from rice-rice to rice-non rice crop based cropping systems [31] in India. Cropping system intensification from double (rice-rice or rice-wheat) to triple cropping system (Wheat-Mungbean-T. Aman) increased the system REY by 10-75% in the High Ganges River Floodplain and Madhupur tract of Bangladesh [5,32,33]; three times more in the active Brahmaputra-Jamuna Floodplain Chars of Bangladesh [34], but 42% more wheat equivalent yield (WEY) in India [35], as well 82% higher system REY when compared to double to four crop-based systems [36]. In other, reported that cropping system intensification from three to four crop-based system increased system REY by 38-44% across the different agroecological zones of Bangladesh [37][38][39], similar to our study, whereas it was lower by 26% [40] and much higher (81%) as reported by Islam et al [41] compared to our study.…”
Section: Crop and System Rice Equivalent Yieldmentioning
confidence: 99%